OPTIMASI BAHAN POLIMER PEMBENTUK MATRIKS TABLET SUSTAINED RELEASE Na. DIKLOFENAK - Audia Triani Olii; Aztriana Aztriana (Fakultas Farmasi UMI, 2015)
Sustained release tablet is one of drug delivery system with an extended release drugs which use polymer to control the release of drug from its dosage form. The advantages of this dosage form is can produce fixed blood levels are without repeat the administration of the unit dose. The aim of this study is to obtain the most optimum polymer as a matrix in sustained release tablets of Diclofenac Sodium. Sustained release tablets made by direct compression method from a mixture of three types of polymer combinations. F1 consists of a combination of HPMC polymer: Etilsellulosa, F2 is the combination of HPMC: Xanthan Gum and F3 consists of a combination of HPMC polymer: Na. Alginate. Each combination of polymer use the same ratio is 1: 2. Tablet evaluations include the weight uniformity of tablet, size,drug content and dissolution test. Result showed that the most optimum combination of polymer as a sustained release tablet matrix is F1 even F2 have an optimum dissolution.